In vitro evaluation of the effectiveness of acidic fluoride dentifrices - Alves, K. M. R. P.; Pessan, Juliano Pelim [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Franco, K. S.; Oliveira, F. A. L.; Buzalaf, M. A. R.; Sassaki, K. T.; Delbem, Alberto Carlos Botazzo [UNESP] (Karger, 2007)
This study evaluated the effectiveness of acidic low-fluoride dentifrices compared to conventional neutral dentifrices. Enamel blocks were submitted to pH cycling and treatment with slurries of dentifrices containing 0, 275, 412, 550 and 1,100 mu g F/g (pH 4.5 or 7.0), and also a commercial dentifrice (1,100 mu g F/g) and a commercial children's dentifrice (500 mu g F/ g). Variations in surface microhardness and in the mineral content in enamel after pH cycling were calculated. Enamel blocks treated with acidic dentifrices exhibited less mineral loss compared to neutral dentifrices (ANOVA; p < 0.05). The acidic dentifrices with 412 and 550 mu g F/g had the same effectiveness as the neutral 1,100-mu g F/g dentifrice and commercial 1,100-mu g F/g dentifrice. Copyright (c) 2007 S. Karger AG, Basel
Keywords: demineralization; dental caries, prevention and control; dentifrices; fluoride; pH